Teilhard De Chardin, the "Six Propositions," and the Holy Office - Kemp, Kenneth W. (Zygon, 2019)
Between 1924 and 1937, the Jesuit Curia in Rome repeatedly placed restrictions on what Jesuit priest-paleontologist Pierre Teilhard de Chardin was allowed to write on those aspects of human origins that, in the view of the Curia, had theological as well as scientific aspects. In 2018, David Grumett and Paul Bentley published an account of the first of those restrictions, together with a previously undiscovered document associated with that restriction. This article corrects a relatively important error in their historical narrative, offers an alternative to their comments about the case, and concludes by embedding the events of 1924-1925 in a slightly larger history of Teilhard's relations with the Jesuit Curia and with the Holy Office. That larger narrative shows that, while Grumett and Bentley's account was mistaken about the involvement of the Holy Office in the case they discuss, it was not wrong about the concerns of that Congregation in questions of human origins.